On the exponential ultradistribution semigroups in Banach spaces - M. Kostic, S. Pilipovic, D. Velinov (Faculty of Sciences and Mathematics, University of Nis, Serbia, 2015)
In this paper, we continue our previous research studies of exponential ultradistribution semigroups in Banach spaces. The existence and uniqueness of analytical solutions of abstract fractional relaxation equations associated with the generators of exponential ultradistribution semigroups have been considered. Some other results are also proved.
Keywords: exponential ultradistribution semigroups, tempered ultradistributions, abstract fractional Cauchy problem